2005
DOI: 10.1142/s0218625x05007074
|View full text |Cite
|
Sign up to set email alerts
|

PREPARATION AND PHOTOVOLTAIC PROPERTIES OF Ag2O/Si ISOTYPE HETEROJUNCTION

Abstract: Highly (101)-oriented p-Ag 2 O thin film with high electrical resistivity was grown by rapid thermal oxidation (RTO) on clean monocrystalline p-type Si without any post-deposition annealing. From optical transmittance and absorptance data, the direct optical band gap was found to be 1.46 eV. The electrical and photovoltaic properties of Ag 2 O/Si isotype heterojunction were examined in the absence of any buffer layer. Ideality factor of heterojunction was found to be 3.9. Photoresponce result revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…The visible light incident on ZnO/Si heterojunction passes through ZnO layer, get absorbed by silicon substrate and then e-h pairs are generated near the ZnO-Si interface. 27 Figure 8 demonstrates the spectral responsivity ðR Þ plots of the ZnO/p-Si structure prepared at di®erent annealing times for the wavelength range (350-900) nm at 7.5 V reverse bias. There are two peaks of response located at 650 nm and 870 nm with maximum responsivity of 0.39 A/W at 875 nm for the photodetector annealed for 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…The visible light incident on ZnO/Si heterojunction passes through ZnO layer, get absorbed by silicon substrate and then e-h pairs are generated near the ZnO-Si interface. 27 Figure 8 demonstrates the spectral responsivity ðR Þ plots of the ZnO/p-Si structure prepared at di®erent annealing times for the wavelength range (350-900) nm at 7.5 V reverse bias. There are two peaks of response located at 650 nm and 870 nm with maximum responsivity of 0.39 A/W at 875 nm for the photodetector annealed for 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the self‐redox reaction of Ag 2 O may occur under the influence of indoor light. Ag 2 O is a p‐type semiconductor 38. The photo‐generated electrons and holes in Ag 2 O may facilitate its redox reaction towards the formation of Ag NPs and oxygen gas, as indicated in Equations 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of annealing duration on the ideality factor calculated forward bias I-V characteristic was observed is in the range of those reported for ITO/ poly(3,4,ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)/poly(2-methoxy-5-(2-ethlhexyloxy))-1,4-phenylenevinylene)(MEH-PPV)/Alq3/Lif/Au Schottky diode [24], and comparable to that those reported for ITO/MEH-PPV/A21 [28]. Large values of ideality factor were obtained due to the presence of recombination in the junction deposition or at junction interface [25], besides some structural defects and lattice mismatch between ZnO and CuGaO2 [19]. The improvement of the device performance is attributed to the smoother surface [26].…”
Section: Methodsmentioning
confidence: 62%